2019
DOI: 10.1016/j.firesaf.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Fire tests on glued-laminated timber beams with specific local material properties

Abstract: The fire resistance of glued-laminated timber (glulam) beams is usually determined by calculation models or by tests. The evaluation of the fire resistance tests is accompanied by an uncertainty with regard to the timber material properties, which is, however, important to know when comparing the test results to the effective crosssection method according to EN 1995-1-2. The present paper presents therefore for the first time the results of six fire resistance tests with glulam beams with specific local mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…• On average, the charring rates specified in the NDS and Eurocode F I G U R E 7 Char depths of solid softwood and glulam taken from the literature. 19,21,23,25,43,[46][47][48][49] CLT specimen with 10 mm-thick laminations exposed for up to 71 min.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…• On average, the charring rates specified in the NDS and Eurocode F I G U R E 7 Char depths of solid softwood and glulam taken from the literature. 19,21,23,25,43,[46][47][48][49] CLT specimen with 10 mm-thick laminations exposed for up to 71 min.…”
Section: Discussionmentioning
confidence: 99%
“…Thermocouples installed perpendicular to the isotherms may underestimate the temperature of timber as a result of conduction heat losses through the thermocouple wires, leading to underestimation of charring rate. 8,9 Installation of thermocouples perpendicular to isotherms via a drilled hole is convenient for large-scale specimens, and installation of inlaid thermocouples during cross laminated timber (CLT) panel assembly is not always possible. Other studies have found no effect of the thermocouple direction on temperature readings and calculated charring rates of CLT panels exposed to the standard fire curve.…”
Section: Combustion Of Timbermentioning
confidence: 99%
See 2 more Smart Citations
“…A layout of the thermocouples inside the timber column is shown in Figure 3. The location of the thermocouples was planned under the viewpoint of the installation parallel to the isotherm 23 . In total 48 thermocouples were installed in the timber column with 16 thermocouples per section.…”
Section: Timber Columnsmentioning
confidence: 99%